Effects of diaphragmatic breathing and pursed lip breathing exercises on the pulmonary function and walking endurance in patients with chronic stroke: a randomised controlled trial. (2nd August 2022) - Yoon, Jeong-Min; Im, Sang-Cheol; Kim, Kyoung
Abstract : Background/Aims: Neurological dysfunction from stroke affects not only the muscles of the extremities and trunk, but also the respiratory function, so it is important to improve the respiratory function of patients with stroke is recognised as an important part. The aim of this study was to investigate the effects of diaphragmatic and pursed lip breathing exercises on pulmonary function, chest expansion and walking endurance in older patients with chronic stroke. Methods: The participants were 32 older patients with chronic stroke, randomly assigned to two groups. The study group ( n =16) performed diaphragmatic breathing exercises in combination with pursed lip breathing exercises, while the control group ( n =16) performed non-resistant cycle ergometer exercises. Forced vital capacity, forced expiratory volume in 1 second, the ratio of forced expiratory volume in 1 second FEV1 to forced vital capacity, peak expiratory flow, chest expansion and 6-Minute Walk Test measurements were taken before and 4 weeks after treatment. Results: The breathing exercise group exhibited a significant increase in chest expansion and 6-Minute Walk Test outcome measurements ( P <0.05). There was a significant difference in forced vital capacity, forced expiratory volume in 1 second and peak expiratory flow between the two groups ( P <0.05). Conclusions: Diaphragmatic breathing and pursed lip breathing exercises were effective in improving pulmonary function in older patients with chronic stroke.